STRATEGI PEMBELAJARAN BERDIFERENSIASI DALAM MEMENUHI KEBUTUHAN BELAJAR PESERTA DIDIK - Feny Rahma Maulidia; Aulya Nanda Prafitasari (ScienceEdu, 2023)
Differentiated Learning Strategies (SPB) have become a popular approach in meeting the learning needs of diverse students. The purpose of this study was to conduct a literature review on SPB and how this strategy can be effective in meeting students' learning needs. The literature review method is used to collect and analyze articles, books, and other sources relevant to this topic. This study shows that SPB is an approach that involves the use of different strategies and approaches to meet the learning needs of individual students. Several strategies that are often used in SPB include reverse teaching, flexible grouping, different assignments, and the use of different resources. Research also shows that SPB can increase student motivation, engagement, and learning outcomes. Keywords: differentiated learning strategy, learning needs, literature review, education